MicroRNA control of stem cell reconstitution and growth in root regeneration - Baulies, Julia; Rodríguez, R. E.; Lazzara, F. E.; Liebsch, Daniela; Zhao, Xin’Ai; Zeng, Jian; Bald, Lotte; Schommer, Christoph; Lohmann, Jan U.; Palatnik, J. F. (Nature plants, 2025)
Plants display a remarkable regeneration capacity, which allows them to replace damaged or lost cells, tissues and organs, and thus recover from a broad spectrum of injuries1,2. Even lost stem cells can be regenerated from non-stem cells after competence acquisition, highlighting the enormous plasticity of plant cells. However, the molecular mechanisms underlying this process are still poorly understood. In the root, the highly conserved microRNA miR396 and its targets, the GROWTH-REGULATING FACTORs (GRFs), control the transition from stem cells to proliferative cells. miR396 promotes stem cell activity by repressing and excluding the GRFs from the stem cell area. In turn, the GRFs promote cell division in the proliferation zone3. Here we show that the miR396-GRF regulatory module guides stem cell reconstitution after root tip excision, playing a dual role: while miR396 promotes competence, the GRFs control regeneration speed. Moreover, plants with ectopic miR396 expression have defined stem cell niches before the excision but do not reconstitute them afterwards, remaining in an open state despite continuing to grow. We propose that this phenomenon is caused by dispersed stem cell activity, which supports growth after root tip excision without reconstituting the organized and spatially restricted stem cell niche typical of Arabidopsis roots.